HUBUNGAN MEKANISME KOPING DAN KUALITAS TIDUR DENGAN TINGKAT KECEMASAN PADA MAHASISWA KEPERAWATAN TINGKAT AKHIR DI UNIVERSITAS INDONESIA MAJU TAHUN 2023 - Sri Wulan Lidia Hia; Astrid Novita; Bambang Suryadi (JOURNAL SAINS STUDENT RESEARCH, 2024)
Introduction :Based on the results of a preliminary study, 80% of students said they often experienced anxiety, had difficulty sleeping and had difficulty concentrating when working on their final assignments, and 20% of students said that anxiety appeared occasionally. Final year students who are writing a thesis are characterized by the fact that they are starting to feel inferior, feeling stupid, feeling unable to complete the thesis, thinking starting to feel uneasy, feeling sad, not feeling confident about what they are doing, often having headaches, and often feeling irritated or irritable to get angry. Objective:To determine the relationship between coping mechanisms and sleep quality and anxiety levels in final year nursing students who are working on their thesis at the University of Indonesia Maju in 2023. Method: This research uses quantitative methods with a descriptive correlation design with a cross sectional approach. The population taken was final year nursing students at the University of Indonesia Maju, class of 2020, totaling 144 respondents. The sampling technique used a non-probability sampling technique, namely purposive sampling, using the lemeshow formula so that a sample of 66 respondents was obtained. Data analysis used the chi-square test with the help of the SPSS application on the computer. Results :1.The Pearson Chi Square results of the relationship between coping mechanisms and anxiety levels in final year nursing students were (p value=0.001) a ˂ 0.05. 2. Pearson Chi Square results of the relationship between sleep quality and anxiety levels in final year nursing students are (p value=0.000) a ˂ 0.05. Conclusion: In this study there was a relationship between coping mechanisms, sleep quality and anxiety levels.